ANALYSIS OF TEMPERATURE STABILITY THERMOGUN CALIBRATOR WITH FUZZY-PID CONTROL - setyawanto, nanda dwi; Wisana, I Dewa Gede Hari; Setiawan, Singgih Yudha (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2025)
Body temperature is an important parameter in medical diagnosis. Thermogun, a non-contact temperature measuring device based on infrared technology, needs to be calibrated periodically to maintain measurement accuracy. This study aims to design a Thermogun calibrator with FUZZY-PID control that uses water as a temperature stabilizer. This system is designed to maintain temperatures in the range of 32°C to 45°C. Testing of the device was carried out using the DS18B20 sensor, as well as the Arduino Mega 2560 microcontroller as the main controller, heater plate for heating and using the Nextion LCD for its display. The test results showed that the system was able to increase the speed of temperature increase with a low level of measurement error (error). From the results of the module data analysis on the standard thermometer, the temperature error using the standard thermometer was 0% at all settings between 32°C-45°C. from the module to 3 Thermoguns using FUZZY-PID control In the experiment conducted, it was found that thermogun 3 had a good average reading of all temperatures that had been measured on the module with an error between the largest 0.625% at various temperature settings. Then on thermogun 1 & 2 had a fairly large error of up to 3.15%. From the measurement results, it can be concluded that FUZZY-PID control can be used as a temperature stability control on a thermometer calibrator. This study succeeded in achieving the desired temperature with accurate accuracy and the tool functioned properly.